Development and Implications of Arabic-Indonesian Dictionaries on Arabic Language Learning - Fitrianingsih, Rahmawati (Pascasarjana Universitas Islam Negeri Mataram, 2024)
This research aims to investigate how the development of Arabic and Indonesian dictionaries influences the learning of Arabic in Indonesia. The research method employed is qualitative with a content or historical research approach, utilizing data collection techniques such as heuristics, documentation, interpretation, and historiography. The history of Arabic lexicography in Indonesia began with three initial dictionaries: Kamus Al Inarah Al Tahzibiyah, Kamus Idris Al Marbawi, and Kamus al Zahabi. Subsequently, newer Arabic-Indonesian dictionaries emerged, including Kamus Indonesia-Arab Al Kalali, Kamus Al Munawwir, and Technology-Based Dictionaries, which are also the focus of this study. This research aims to explore the development and implications of these dictionaries on the Arabic language learning process in Indonesia, aiming to provide a deeper understanding of their contributions within the context of Arabic language education in Indonesia.